2020
DOI: 10.1186/s12906-020-03177-y
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotective effects of polydatin against myocardial injury in diabetic rats via inhibition of NADPH oxidase and NF-κB activities

Abstract: Background Diabetic cardiomyopathy is a main cause of the increased morbidity in diabetic patients, no effective treatment is available so far. Polydatin, a resveratrol glucoside isolated from the Polygonum cuspidatum, was found by our and others have antioxidant and cardioprotective activities. Therapeutic effects of polydatin on diabetic cardiomyopathy and the possible mechanisms remains unclear. This study aimed to investigate the cardioprotective effects and underlying mechanisms of polydat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 52 publications
0
17
0
Order By: Relevance
“…Chronic hyperglycemia provokes an increased cardiac injury and decreased cardiomyocyte viability ( Tan YY. et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Chronic hyperglycemia provokes an increased cardiac injury and decreased cardiomyocyte viability ( Tan YY. et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…mTOR could improve the autophagy activity and reduce the apoptosis of chondrocytes in a KOA, further reduce the degree of OA [28]. It has been proved that polydatin regulated important molecules involved in autophagy and in ammation signaling pathways in bovine mammary epithelial cells [29], acute kidney injury [30,31] and myocardial injury in diabetic rats [32,33]. In this study, it was found that the effects of polydatin on autophagy induction was mTORdependent and regulated by AMPK.…”
Section: Abbreviationsmentioning
confidence: 81%
“…A recent study demonstrated that polydatin reduces tissue damages induced by hyperglycemia and hyperlipidemia, increasing cardiovascular functions during diabetes (86,87). In another preclinical trial, 8-weeks polydatin treatment significantly improved the diastolic and systolic dysfunction, attenuated hypertrophy and interstitial fibrosis in mice with diabetes (88). Other similar studies suggested that polydatin protects cardiomyocytes heart failure also in non-diabetic models through reduction of iROS, pro-inflammatory prostaglandins and cytokines (89, 90).…”
Section: Discussionmentioning
confidence: 93%